Efisiensi Anggaran Pendidikan dan Akuntabilitas Dana BOS terhadap Peningkatan Mutu Pendidikan - Selviana Al-Jannah; Qolbi Khoiri (Departement of Mathematics Education, 2023)
This study analyzes the efficiency of the Education Budget and the Accountability of the Use of School Operational Assistance Funds (BOS) to Improve the Quality of Education. One of the government's ways of alleviating poverty is by improving the quality of education, the method taken is through increasing the budget for the education sector. The purpose of this research is to determine the efficiency of the budget and the accountability of BOS funds for improving the quality of education. This research method uses the Systematic Literature Review method ( SLR). in this article it was found that there was an increase in the quality of education with the BOS funding education budget.